BH3 peptides induce mitochondrial fission and cell death independent of BAX/BAK. - Emelyn H Shroff (PLoS ONE, 2009)
BH3 only proteins trigger cell death by interacting with pro- and anti-apoptotic members of the BCL-2 family of proteins. Here we report that BH3 peptides corresponding to the death domain of BH3-only proteins, which bind all the pro-survival BCL-2 family proteins, induce cell death in the absence of BAX and BAK. The BH3 peptides did not cause the release of cytochrome c from isolated mitochondria or from mitochondria in cells. However, the BH3 peptides did cause a decrease in mitochondrial membrane potential but did not induce the opening of the mitochondrial permeability transition pore. Interestingly, the BH3 peptides induced mitochondria to undergo fission in the absence of BAX and BAK. The binding of BCL-X(L) with dynamin-related protein 1 (DRP1), a GTPase known to regulate mitochondrial fission, increased in the presence of BH3 peptides. These results suggest that pro-survival BCL-2 proteins regulate mitochondrial fission and cell death in the absence of BAX and BAK.